2020
DOI: 10.4236/jhrss.2020.81004
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Impact of Training and Development on Organisational Performance: A Case Study of the Gauteng Provincial Department of Economic Development

Abstract: Orientation: Organisations relies on the expertise, standard, competence and performance of its employees for it to offer effectual service delivery. However, the framework and administration of Training and Development has not advanced in parallel to the new and ever changing business needs. Research purpose: The purpose of this study is to evaluate the impact of Training and Development on organisational performance using a case study, literature review and statistics of the Department of Economic Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The findings agree with Mdhlalose's (2020) conclusions that organizations should improve mentorship programs to guarantee that their staff can stay up with the current advances in order to survive the harsh competition. In this day and age of fast social and political change, appeals for school reform may be heard all around the world.…”
Section: Resultssupporting
confidence: 86%
“…The findings agree with Mdhlalose's (2020) conclusions that organizations should improve mentorship programs to guarantee that their staff can stay up with the current advances in order to survive the harsh competition. In this day and age of fast social and political change, appeals for school reform may be heard all around the world.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, the model exhibited that a unit increase in performance and rewards management would lead to lead to .145 increase in Organizational Performance and a unit increase in Employee Welfare would lead to .191 increase in Organizational Performance at the Zambia National Assembly. Mdhlalose (2020) [34] also found that Training and Development has a positive impact on the overall. In a study on SHRM practices and organizational performance, Gituma and Beyene (2018) [22] , found that performance appraisal positively influence performance.…”
Section: Regression Results For Shrm and Organisational Performancementioning
confidence: 98%
“…This was shown by an average mean score of 3.57 in the descriptive statistics on the impact of learning and development. Mdhlalose (2020) conducted a study with the aim of evaluating the impact of Training and Development on organisational performance. Among the findings of the study, it was found that employee's performance increases after completing a training programme.…”
Section: Findings On the Impact Of Learning And Developmentmentioning
confidence: 99%
“…Therefore, it was concluded that the aspect of learning and development among strategic human resource management practices at the National Assembly had a positive impact on organisational performance. Mdhlalose (2020), in a study conducted to evaluate the impact of training and development on organisational performance, found that training and development had a positive impact on the overall performance of the workforce within the department that was under study.…”
Section: Findings On the Impact Of Learning And Developmentmentioning
confidence: 99%